2007
DOI: 10.1007/s10562-007-9260-0
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Performance of Monolithic Foam Ni/SiC Catalyst in Carbon dioxide Reforming of Methane to Synthesis Gas

Abstract: Carbon dioxide reforming of methane to synthesis gas has been investigated with Ni catalysts supported on monolithic foam SiC, which were prepared by the initial wetness impregnation method. The catalyst of 7 wt%Ni/ SiC was verified to be the best one in different Ni content catalysts. Compared with other catalysts such as 7 wt%Ni/ SiO 2 and 7 wt%Ni/Al 2 O 3 , the 7 wt%Ni/SiC catalyst exhibited not only the highest activity but also remarkable stability and excellent coke resistance during 100 h reaction. Furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 32 publications
1
9
0
2
Order By: Relevance
“…[42,43]. The SiC sample is observed to exhibit peaks of the dominant SiC phase [44]. The Pd@ZSM-5/SiC shows the XRD patterns of both SiC and MFI zeolite, in good agreement with that of the zeolite coated on the SiC support.…”
Section: Hydrodeoxygenation Of Methyl Oleatesupporting
confidence: 55%
“…[42,43]. The SiC sample is observed to exhibit peaks of the dominant SiC phase [44]. The Pd@ZSM-5/SiC shows the XRD patterns of both SiC and MFI zeolite, in good agreement with that of the zeolite coated on the SiC support.…”
Section: Hydrodeoxygenation Of Methyl Oleatesupporting
confidence: 55%
“…It is a very promising catalyst support in place of the traditional insulated supports in highly endothermic or exothermic reactions [15,16]. SiC has been proved to be a superior catalyst support in many different reactions, e.g., methane reforming [17][18][19][20][21], automotive exhaust treatment [22][23][24], methane combustion [25][26][27], butane oxidation [28], Fischer-Tropsch synthesis [29][30][31], oxidative coupling of methane [32], isomerization [33], and dehydrogenation [34]. However, to the best of our knowledge, SiC support is less employed in the methanation reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, the same team reported few years later on the performance of a noble metal-free Ni/MgO-Al 2 O 3 catalyzed SiC foam composite as one of the most promising solar absorbers for a reformer unit. 353 Wang and co-workers reported in the same years the advantages of SiC as an active-phase carrier for non-noble metals in the process within a more classical reactor 355 This suggested that rWGS occurred simultaneously and more significantly on the metal oxide catalytic systems. On the other hand, the hydrophobic nature of silicon carbide was supposed to remove faster the adsorbed water at its surface, 356 thus limiting the rWGS process to occur.…”
Section: Catalytic Applicationsmentioning
confidence: 98%